Chemical burns of gingiva and its management - M M Dayakar; Prakash G Pai; Radhika Priyadarshini M Sooranagi; Vintu Vijayan; Abdul Waheed (Wolters Kluwer Medknow Publications, 2018)
Chemical burns on the gingiva can be caused by the use of certain pharmaceutical and nonpharmaceutical products by patients or by injudicious use of caustics by the dental clinician. These lesions in the oral cavity, however, are rarely reported. Hence, information about the product and needful instructions is necessary to be given to the patients for prevention of the same. These burns can be caused by the way of self-infliction, allergic tendency toward certain products, or it may be iatrogenic. A detailed history is the key to diagnosing and managing these cases. Chemical burns are usually treated by eliminating the etiology and managed by palliative therapy.